Aksi Mahasiswa Kkn Kolaboratif Jember Mencegah Pernikahan Dini Di Desa Sukorambi - Diego Rafi Putra Uta; Yuldani Adinda Daviyana; Aprisyah Darwa Dita; Dimas Fahrur Rozi; Muhammad Fattah Shiddiq; Irma Kusumawati; Novia Lailatus Safitri; Siti hotimah; hidayaturrokhman hidayaturrokhman; Hildatus Zakiah; Sita Laila Anggraeni; Ahmad Firdaus (Jurnal Informasi Pengabdian Masyarakat, 2023)
Indonesia is one of the countries with the highest number of early marriages in the world due to several factors, one of which is social and cultural. Early marriage can be interpreted as a marriage carried out by a husband and wife aged less than 17 years. The early marriage rate in East Java according to the 2017 Susenas reached 18.44%. Jember Regency is one of the biggest contributors to the number of early marriages in East Java with a total of 1,400 out of 21,000 marriages in 2021. Sukorambi Village is a village located under Argopuro's feet with various tribes and cultures and the majority has currency in agriculture. Therefore, in reducing the number of early marriages, the implementation of counseling related to early marriage with the main target is students who are pursuing senior secondary education in the hope that there will be awareness of damaging early marriage and reducing the number of early marriages in Sukorambi Village.